Navigational Aids Systems (Navaids) and Safety Measures of Aircraft : an Analysis. - Hassan Adegbayi M; Osoba Sunday E (Faculty of Geography, Universitas Gadjah Mada, 2016)
Abstract This study examines the availability of necessary NAVAIDS required for safe approach and landing; highlight the accidents and incidents occurrences relating to the final approach amongst others. A combination of both primary data and secondary data were employed in the study and findingsshows that there are varying degree of fluctuations in number of aircraft using NAVAIDS in Nigeria from 2003 to 2013 and that there is strong and positive correlation (r< +0.97) in the relationship between the total aircraft and those that uses precision NAVAIDS for final approach and landing during that period. So also, there is strong positive correlation (r< 0.95) between total accidents and incidents and Approach-Landing accident and incidents between 1968 and 2012. The study recommends adequate precision approach NAVAIDS in line with International Civil Aviation Organisation (ICAO) recommendation and policy formulation on replacement of ageing and obsolete NAVAIDS in Nigerian airports among others. Abstrak Penelitian ini menguji ketersediaan NAVAIDS yang diperlukan untuk pendekatan dan pendaratan yang aman, khususnya pada kecelakaan dan insiden yang berkaitan dengan pendekatan akhir diantara yang lain. Kombinasi data primer dan sekunder digunakan dalam penelitian dan menunjukkan bahwa ada berbagai tingkatan fluktuasi jumlah pesawat yang menggunakan NAVAIDS di Nigeria dari tahun 2003 sampai 2013 dan menunjukkan adanya hubungan yang kuat dan positif (r< +0,97) antara total pesawat dan ketelitian menggunakan NAVAIDS untuk pendekatan akhir dan pendaratan selama periode tersebut. Terdapat pula korelasi positif kuat (r< 0,95) antara total kecelakaan dan insiden dengan pendekatan-pendaratan kecelakan dan insiden antara 1968 dan 2012. Penelitian ini merekomendasikan ketelitian menggunakan NAVAIDS untuk pendekatan sesuai dengan Organisasi Penerbangan Sipil Internasional (ICAO) dan perumusan kebijakan penggantian NAVAIDS yang usang dan tua di bandara Nigeria lainnya.